2013
DOI: 10.1590/s1414-81452013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Possível impacto da "Lei Seca" nos atendimentos a vítimas de acidentes de trânsito em uma unidade de emergência

Abstract: Estudo quantitativo descritivo, cujos objetivos foram: determinar o número de indivíduos vítimas de acidentes de trânsito atendidos em um setor de emergência de um hospital municipal do Rio de Janeiro antes e depois da implementação da "Lei Seca" e identificar o perfil dessa população e as características dos acidentes de trânsito, estimando sua prevalência antes e após a vigência da "Lei Seca". Foram analisados 1.531 prontuários relativos aos acidentes de trânsito ocorridos no ano de 2007 e 2009. Houve preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
2
4
0
11
Order By: Relevance
“…These facts support the findings of 75 cases of traffic accidents (47%). Confirming the results of this study, other authors (18) (18). Similarly, Mendes et al (6) in their study on the use of seat belts related to maxillofacial trauma pointed out that Brazil was one of the countries with the highest prevalence of people injured in traffic accidents with 18.3 victims per 100,000 inhabitants in 2008, and the results showed that men were twice as likely to use security equipment than women, either as a driver or as a passenger.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These facts support the findings of 75 cases of traffic accidents (47%). Confirming the results of this study, other authors (18) (18). Similarly, Mendes et al (6) in their study on the use of seat belts related to maxillofacial trauma pointed out that Brazil was one of the countries with the highest prevalence of people injured in traffic accidents with 18.3 victims per 100,000 inhabitants in 2008, and the results showed that men were twice as likely to use security equipment than women, either as a driver or as a passenger.…”
Section: Discussionsupporting
confidence: 92%
“…These facts support the findings of 75 cases of traffic accidents (47%). Confirming the results of this study, other authors investigated 1531 records from traffic accidents in 2007 and 2009 in the North District of Rio de Janeiro and observed a prevalence of 40.2% due to motorcycle accidents in 2007 and 42.3% in 2009, while car accidents were 22.1% and 23.4% in 2007 and 2009, respectively . Similarly, Mendes et al in their study on the use of seat belts related to maxillofacial trauma pointed out that Brazil was one of the countries with the highest prevalence of people injured in traffic accidents with 18.3 victims per 100,000 inhabitants in 2008, and the results showed that men were twice as likely to use security equipment than women, either as a driver or as a passenger.…”
Section: Discussionsupporting
confidence: 84%
“…[7][8][9] O aumento no número de acidentes de trânsito representa significativo impacto na economia mundial, não só pelos altos custos com atendimento e internação das vítimas, mas também por ser responsável pela morte de expressiva parcela da população economicamente ativa, uma vez que o perfil das vítimas fatais tem sido majoritariamente de pessoas do sexo masculino e de faixa etária adulta produtiva. 10 Ressalta-se ainda que a ocorrência de vítimas por esses acidentes -mortas, feridas ou incapacitadas -afeta, também, familiares e amigos, pois muitas famílias têm sua renda diminuída pela perda do financiador, tendo que arcar com custos e cuidados. 11 A relação entre álcool e acidentes de trânsito tem sido associada a índices significativos de óbitos e de vítimas de traumas atendidas com alcoolemia positiva.…”
Section: Introductionunclassified
“…[21][22] Associated with behavior in traffic, another research carried out with the child and adolescent population points to a greater chance of road traffic accidents by motorcyclists on Sundays, Saturdays and Fridays due to the abuse of alcoholic beverages. 5 According to the 2 nd National Survey on alcohol and drugs conducted in 2006 and 2012, the onset of "drinking" is becoming more precocious and women are drinking more.…”
Section: Resultsmentioning
confidence: 99%